Marketing in university-industry technological collaboration : communication and research commercialization - Grzegorczyk, Malgorzata A. (Palgrave pivot, 2021)
This book explores the diverse roles that marketing can, and should, play in modern, twenty-first century technology transfer in university-industry collaborations. Using various marketing lenses, it takes readers through the challenges of technology transfer and commercialization of science-based innovations. It presents research based, but practice-focused, conclusions relating to marketing implementation at different stages of the commercialization process. The author suggests that marketings strategic role spans the whole process from idea generation, development, valuation, customer matching and marketization. Such approaches can improve the effectiveness of public money spent on research, university-industry cooperation, and research commercialization. The book will appeal to students, university teachers and researchers in a wide range of fields including: technology management, innovation, marketing, and science commercialization. It will also be of interest to those concerned directly with the practices of university technology transfer and commercialization, such as the employees, and leaders of technology transfer offices and researcher-entrepreneurs. Dr Malgorzata Anna Grzegorczyk is Senior Lecturer at Nottingham Business School, Nottingham Trent University, UK and Assistant Professor at University of Lodz, Poland.